2006
DOI: 10.1016/j.neuron.2005.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Layer-Specific Targeting by Reciprocal Expression of a Cell Adhesion Molecule, Capricious

Abstract: Layer-specific innervation is a major form of synaptic targeting in the central nervous system. In the Drosophila visual system, photoreceptors R7 and R8 connect to targets in distinct layers of the medulla, a ganglion of the optic lobe. We show here that Capricious (CAPS), a transmembrane protein with leucine-rich repeats (LRRs), is a layer-specific cell adhesion molecule that regulates photoreceptor targeting in the medulla. During the period of photoreceptor targeting, caps is specifically expressed in R8 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
95
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 29 publications
6
95
2
Order By: Relevance
“…To address this, we performed cell aggregation experiments using transfected S2 cells. S2 cells have low adhesivity and are widely used to determine the binding property of cell adhesion molecules (Shinza-Kameda et al, 2006). S2 cells were transiently transfected with GFP control and Tutl-GFP fusion constructs.…”
Section: Tutl Mediates Homophilic Cell-cell Interactions In Transfectmentioning
confidence: 99%
“…To address this, we performed cell aggregation experiments using transfected S2 cells. S2 cells have low adhesivity and are widely used to determine the binding property of cell adhesion molecules (Shinza-Kameda et al, 2006). S2 cells were transiently transfected with GFP control and Tutl-GFP fusion constructs.…”
Section: Tutl Mediates Homophilic Cell-cell Interactions In Transfectmentioning
confidence: 99%
“…The transcription factor Runt is expressed in R7 and R8, and its misexpression is sufficient to target R2 and R5 to the medulla, suggesting that it controls the choice of optic neuropil (2). Endogenous expression of the homophilic cell adhesion molecule Capricious (Caps) in R8 or its ectopic expression in R7 directs these photoreceptors to terminate in the Caps-positive M3 layer (3). The transmembrane cadherin Flamingo (Fmi) is required for R8 targeting (4,5), whereas loss of either N-cadherin (Ncad) (6) or one of the receptor protein tyrosine phosphatases (RPTPs), PTP69D (7) or LAR (8,9), causes R7 to terminate inappropriately in the R8 layer.…”
mentioning
confidence: 99%
“…The molecular function of both Caps and Trn proteins is still unclear. They appear important in mediating interaction and distinctiveness between groups of cells: neurons finding appropriate targets in the brain (Shishido et al 1998;Shinza-Kameda et al 2006), separation of ventral and dorsal compartment cells in the wing disc (Milan et al 2001), and tracheal morphogenesis across segment boundaries (Krause et al 2006). It has been suggested that Caps and Trn act as homophilic or heterophilic adhesion receptors or serve another unidentified function during adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Both proteins have been implicated in the formation of compartments of cells with different affinities in the wing disc (Milan et al 2001), modulation of epithelial integrity within the wing disc (Mao et al 2008), correct targeting of a subset of photoreceptor axons to the correct layer within the optic lobe (Shinza-Kameda et al 2006), and the joining of tracheal branches over segment boundaries (Krause et al 2006). One study also showed that in tissue culture Capricious and Tartan are able to mediate homophilic cell adhesion, a molecular function that could explain their roles discussed above (Shinza-Kameda et al 2006). Overexpression of capricious using EP(3)552 led to glands with an enlarged lumen and very aberrant shapes at stage 15 (Figure 8, B and C).…”
Section: Analysis Of Individual Genes In Detailmentioning
confidence: 99%